Analysis of the Utilization of Quizizz Learning Media in Improving Students' Understanding and Motivation to Learn the Qur'an and Hadith at MAN 1 Tuban - Nur Aida Fitria Kusuma Putri; Ima Seftiyana Safira; Ikhda Nilla Rosyida; M. Hasbullah (Mazidah: Journal Of Educational Research, 2026)
This study aims to examine the use of Quizizz as a learning medium in Qur’an Hadith instruction and to explore students’ perceptions regarding its impact on learning motivation at MAN 1 Tuban. The research applied a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing techniques. The results reveal that the implementation of Quizizz creates a more interactive, engaging, and enjoyable learning atmosphere. Students show positive responses, as this medium is perceived to enhance learning motivation both intrinsically, through curiosity and challenge, and extrinsically, through features such as points, rankings, and immediate feedback. In addition, Quizizz encourages greater student activity, focus, and participation during the learning process. Despite several technical limitations such as internet connectivity and device availability, Quizizz is generally effective as an innovative learning medium aligned with the demands of digital-era education.